High resolution sagittal T2 in the study of the female pelvis by MRI: comparative study of motion-artifact reduction techniques - Freitas, Davide (2022)
The high contrast resolution, possibility of tissue characterization, multiplanar imaging, lack of ionizing radiation and the increasing availability of scanners, made MRI an important tool in female pelvis diagnostic, specifically in ovarian and uterine pathology. Fasting, empty bladder and compression by a pelvic band, reduce the movement and phase artifacts caused by peristaltic movements of the intestine and other organs (fig.1), as well as pelvic respiratory artifacts. However, other resources, such as the intravenous administration of anti-spasmodic drugs (glucagon or hyoscine butyl-bromide) are often required to increase imaging quality, and its routine application is often recommended . These drugs have few contraindications, such as glaucoma and myasthenia gravis, and low incidence of allergic reactions. The most common side effect is blurred vision, which occurs in about 10 % of the patients and is reversible in 30-45 minutes. The majority of modern MRI scanners include advances in image acquisition, such as the sequences PROPPLER / BLADE (General Electric and Siemens terms, respectively). These sequences have a radial k-space sampling concept with parallel data lines rotating around the k-space center, which allows spatial inconsistencies. Data indicating through-plane motion based on correlation measurement are rejected. Motion artifacts are further reduced through averaging in low spatial frequencies. Thus, considering the side effects that antispasmodic drugs can provoke, and the existence of modern scanners with advanced acquisition techniques that minimize movement artifacts, the aim of our study was to compare image quality, anatomic detail and presence of artifacts on high resolution sagittal T2-turbo-spin-echo (TSE), T2-TSE-BLADE and on T2-TSE after intravenous administration of an antispasmodic drug, hereby referred as T2-TSE-iv, in the female pelvic MRI study.